2021
DOI: 10.1097/mot.0000000000000888
|View full text |Cite
|
Sign up to set email alerts
|

The solid organ transplant recipient with SARS-CoV-2 infection

Abstract: Purpose of review The COVID-19 pandemic is a major challenge to global health, particularly among vulnerable populations. Here, we describe the emerging epidemiology and relevant data on treatment options for COVID-19. We discuss the implications of current knowledge for solid organ transplant (SOT) recipients. Recent findings Risk factors and outcomes of COVID-19 among SOT recipients remain uncertain, but recent data suggest similar outcomes to the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…After initial reports of success, however, most of them failed to improve patient outcomes in randomized controlled trials. To date, there have been no randomized studies among SOT recipients [74]. Reports of specific medications that were used in SOT recipients are described below.…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…After initial reports of success, however, most of them failed to improve patient outcomes in randomized controlled trials. To date, there have been no randomized studies among SOT recipients [74]. Reports of specific medications that were used in SOT recipients are described below.…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
“…Severe illness (i.e., mechanical ventilation or extra corporeal membrane oxygenation-ECMO requirement): dexamethasone (or equivalent steroid) up to 10 days, consider remdesivir for 5 days, and consider reducing or holding antimetabolite [74].…”
mentioning
confidence: 99%
“…Angiotensin-converting enzyme-2 and dipeptidyl peptidase, expressed in proximal tubular cells, are identified as receptors for SARS-CoV and MERS-CoV[ 12 ]. The possible explanation for acute renal injury is the uptake of SARS-CoV-2 virus into the proximal tubular epithelium and virus infection inducing CD68+ -macrophage infiltration and enhancing complement C5b-C9 deposition on tubules[ 13 ].…”
Section: Undesirable Effects Of Immunosuppression On Covid-19 In Tran...mentioning
confidence: 99%
“…Several studies have reported that immunosuppression may be a possible risk factor for coronavirus-related pneumonia in a patient[ 13 ]. For kidney transplant recipients diagnosed with SARS-CoV-2, it may be reasonable to use cyclosporine because of its antiviral and immune modulatory effects[ 13 ].…”
Section: Undesirable Effects Of Immunosuppression On Covid-19 In Tran...mentioning
confidence: 99%
See 1 more Smart Citation